2015
DOI: 10.1128/jvi.01112-15
|View full text |Cite
|
Sign up to set email alerts
|

Arenavirus Coinfections Are Common in Snakes with Boid Inclusion Body Disease

Abstract: e Recently, novel arenaviruses were found in snakes with boid inclusion body disease (BIBD); these form the new genus Reptarenavirus within the family Arenaviridae. We used next-generation sequencing and de novo sequence assembly to investigate reptarenavirus isolates from our previous study. Four of the six isolates and all of the samples from snakes with BIBD contained at least two reptarenavirus species. The viruses sequenced comprise four novel reptarenavirus species and a representative of a new arenaviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(124 citation statements)
references
References 12 publications
9
113
0
2
Order By: Relevance
“…Affinity purification served to produce anti-SDAg and anti-NP (reptarenavirus nucleoprotein, the main antigen present in infected cells), which we directly labeled with Alexa Fluor 488 or Alexa Fluor 594 dyes (anti-SDAg-AF488, anti-SDAg-AF594, anti-NP-AF488, and anti-NP-AF594). Our studies show that the anti-NP antibody can be used to detect all reptarenavirus NPs thus far described (30)(31)(32)(33). As demonstrated in Fig.…”
Section: Resultssupporting
confidence: 58%
“…Affinity purification served to produce anti-SDAg and anti-NP (reptarenavirus nucleoprotein, the main antigen present in infected cells), which we directly labeled with Alexa Fluor 488 or Alexa Fluor 594 dyes (anti-SDAg-AF488, anti-SDAg-AF594, anti-NP-AF488, and anti-NP-AF594). Our studies show that the anti-NP antibody can be used to detect all reptarenavirus NPs thus far described (30)(31)(32)(33). As demonstrated in Fig.…”
Section: Resultssupporting
confidence: 58%
“…For superinfection studies we used two reptarenaviruses: University of Helsinki virus-2 (UHV-2 29 ) and University of Giessen virus-1 (UGV-1 33 ), and one hartmanivirus, Haartman Institute Snake virus-1 (HISV-1 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…Mammarenaviruses distributing worldwide and cause febrile diseases for both humans and animals (Buchmeier et al, 2007). Reptarenaviruses are infected snakes (Hepojoki et al, 2015), were the infection in human have not been reported. Arenaviruses have a segmented ambisense single strand RNA genome, which is typically grouped as negative sense RNA viruses (Buchmeier et al, 2007).…”
Section: Sars and Mers Coronaviruses Ebola Virus Marburg Virus Henmentioning
confidence: 99%